MENINGKATKAN KEMAMPUAN MENULIS MELALUI METODE MULTISENSORI PADA ANAK KESULITAN BELAJAR - Nini Permatasari (Universitas Negeri Padang, 2014)
Abstract : This research is motivated by the presence of a child learning disabilities who have difficulty writing nouns in SDN 09 Koto Outer district. Padang Pauh. The purpose of this study so that the children can write words with multisensory. Mulisensori is where children in learning through more than one of the five senses ie visual (vision), taktile (feeling), kinesthetic (movement), audiotory (auditory). Therefore, researchers interested in attracting this problem so that the child is able to write the words correctly so that the learning process can be run well. Keyword: Menulis; anak kesulitan belajar; multisensori